2020
DOI: 10.1002/ardp.202000209
|View full text |Cite
|
Sign up to set email alerts
|

Cell death‐inducing properties of selected dendrimers against different breast cancer and leukemia cell lines

Abstract: Dendrimers represent an opportunity for targeted drug delivery into tumor cells. This is facilitated, for example, by loading of dendrimers with anticancer compounds. However, to assess the effects caused by such conjugates, knowledge of the cytotoxicity of the dendrimers themselves is necessary. The poly(amido amine)-derived dendrimers G 1 (Phe) 6 , G 1 (Dan) 3 , and G 2 were selected due to their different numbers of free amino groups and the poly(propylene imine) (PPI) dendrimer PPI-G 3 served as a referenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
(70 reference statements)
0
4
0
Order By: Relevance
“…The fluorescence intensity profile shows a higher cell death in MDA MB 231 cells compared to that of A549 and HepG2 cells in all three coordination entities. Coordination entity RuG0 has exhibited a higher cell death in all three cell lines; this may infer that RuG0 disrupts the cell membrane and induces cell death by a necrosis mechanism compared to other coordination complexes …”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…The fluorescence intensity profile shows a higher cell death in MDA MB 231 cells compared to that of A549 and HepG2 cells in all three coordination entities. Coordination entity RuG0 has exhibited a higher cell death in all three cell lines; this may infer that RuG0 disrupts the cell membrane and induces cell death by a necrosis mechanism compared to other coordination complexes …”
Section: Resultsmentioning
confidence: 92%
“…The ability of PI to stain the cells depends upon the integrity of its cell membrane; therefore, PI cannot stain a live or early apoptotic cells. 65 This is clearly evident from the coordination entity-untreated control experiments, wherein very little or no red stains are observed; this indicates that the cell membranes are intact and do not allow the passage of PI. In cases of RuG0-, RuG1-, and RuG2-treated cell lines, stronger red images are observed indicating the presence of death cells; it is clearly concluded that on treatment with the coordination entities the integrity of the cell membrane is lost, and PI very well gets access to the DNA molecules and emits strong red fluorescence.…”
Section: Fluorescence Imaging Studies 341 Apoptotic Morphological Ana...mentioning
confidence: 93%
“…[ 17 ] This paves the way for future conjugation of the complexes to dendrimers or polymers by ester binding to enable targeted drug delivery. [ 18 ]…”
Section: Introductionmentioning
confidence: 99%
“…[17] This paves the way for future conjugation of the complexes to dendrimers or polymers by ester binding to enable targeted drug delivery. [18] Also [Fe(II)SAP] complexes demonstrated outstanding apoptotic activity against U-937 non-Hodgkin's lymphoma, HL-60, and K-562 leukemia cells. [19] As [Co(III)SAP] mimics isoelectric conditions of [Fe (II)SAP] and cobalt is, like iron, also a member of the iron triad, this metal was selected for further analysis in this study.…”
mentioning
confidence: 99%